Plio-Pleistocene Small Mammal-Based Biochronology of Eastern Anatolia and Transcaucasus - Tesakov, Alexey S.; Frolov, Pavel; Simakova, Alexandra; Yakimova, Albina; Titov, Vadim; Ranjan, Pranav; Trifonov, Vladimir (Mdpi, 2024)
The known Plio-Pleistocene mammalian record, mainly represented by small mammals, and its biotic and geological context in the vast region of Eastern Turkey and Transcaucasus provides a sound base for regional biochronology. Recently obtained faunal associations and the main evolutionary lineages found in the region support direct correlations to the European (ELMA/MN/MQ) and the Eastern European (faunal complexes/MQR-MNR) biochronological systems. Important data on palynology, aquatic and terrestrial mollusks, and magnetostratigraphy integrate the reviewed material into a robust local biochronology. The range of standard biochrons of Early Pliocene through late Early Pleistocene and the regional Anatolian zones M-P are reliably detected. The Early Pleistocene time range (zone P) is refined based on rhizodont lagurines Borsodia and Euro-Asian larger voles Mimomys ex gr. pliocaenicus. The successive zone R for Early Pleistocene faunas with early rootless Microtini is proposed.
Keywords: mammals; biochronology; eastern Turkey; transcaucasus; pliocene; early pleistocene; middle pleistocene